Total Quality Control Analysis on Plywood Using Six Sigma, New Seven Tools, and Kaizen Methods - Nugraha, Isna; Aqidawati, Era Febriana; Nugrahadi, Bekti; Ramadhan, Gilang; Aryanti, Friska (Performa: Media Ilmiah Teknik Industri, 2000)
Control is a form of protection against various undesirable actions or disturbances, both internal and external, that can affect a system. This research aims to analyze defects in plywood products at the JatiMulyo Furniture Store using the Total Quality Control (TQC) method to determine priority problems that must be resolved first. The study adopts a mixed-method approach by combining qualitative and quantitative analyses. A fishbone diagram is utilized to systematically identify possible causes of defects. The findings reveal three main types of defects: cracked plywood (103 units, 32%), unsymmetrical plywood (114 units, 36%), and inappropriate plywood thickness (103 units, 32%), with a total of 320 defective units. No data correction was necessary as all percentages fall within acceptable limits. This thorough analysis enables the identification of key factors affecting product quality and provides direction for continuous improvement. The results are expected to guide quality control efforts. Further improvements can be made using continuous monitoring and corrective action.